Temporal trends in vaccine hesitancy among Caribbean health workers: analysis of 2021 and 2024 surveys - Martha Velandia-Gonzalez; Tamara Rivera; E. Benjamín Puertas; Dale A. Rhoda; Jennifer Brustrom (Revista Panamericana de Salud Pública)
Objective: Although the benefits of vaccination are well established, a minority of health workers (HWs) are vaccine hesitant. Understanding vaccine hesitancy among HWs is crucial for providing them the information and skills they need to promote vaccine acceptance and informed decision-making among the populations they serve. This study aimed to evaluate differences in vaccine hesitancy and attitudes towards vaccines among HWs in the Caribbean between 2021 and 2024. Methods: Two cross-sectional Internet surveys were conducted among HWs in the Caribbean. The first survey was administered early in the COVID-19 pandemic, before COVID-19 vaccines were widely available in the region (April–May 2021). The second survey took place in the post-pandemic era when COVID-19 vaccines were easily obtainable and after countries and the Pan American Health Organization (PAHO) implemented interventions to address vaccine hesitancy (January–March 2024). Results: Caribbean HWs’ attitudes toward all vaccines were relatively more positive in 2024 than in 2021. Notably, the rate of COVID-19 vaccine hesitancy decreased from 26% in 2021 to 5% in 2024, with the largest reductions observed among allied health professionals, the youngest respondents, and nursing professionals. Respondents’ sentiments about vaccines in general and perceptions of vaccines’ effectiveness and safety were also more favorable in the second survey. Conclusions: Improvements in HWs’ attitudes and reduced vaccine hesitancy are likely due to multiple, interactive contextual factors, including increased knowledge about COVID-19 and its vaccine, scientific evidence of vaccine effectiveness, personal experience, and increased health education efforts. While this study did not evaluate specific interventions, findings suggest that well-designed and context-sensitive strategies may contribute to supporting vaccine acceptance among HWs.